Computational Modelling of Fluid Dynamics for Real-world Applications - Mai, Cao Thị; Dũng, Bùi Anh; Tùng, Hoàng Thanh (Etunas Sukses Sistem, 2023)
This study presents an innovative computational framework for modelling fluid dynamics in real-world applications. The proposed approach effectively simulates turbulent flows, fluid-structure interactions, and heat transfer processes by integrating advanced numerical methods with optimised algorithms. The model developed through adaptations of the Navier–Stokes equations, was rigorously validated using comprehensive experimental trials. The experimental results demonstrated that the simulations achieved an accuracy within 5% of the observed measurements, confirming the model’s reliability in replicating complex physical phenomena. These findings not only enhance our fundamental understanding of fluid behaviour but also provide valuable insights for design optimisation and system management across various industrial sectors.